A multi-objective mathematical model and genetic algorithm for reliability analysis in flexible job-shop scheduling problem. (2018) - Aghajani, Aydin; Fouladi, Paria
Problems involving a single objective function are not as realistic as the ones, which involve multi-objective functions. This paper presents a new two objectives mathematical model for flexible job-shop scheduling problem in which the reliability index of machines as an important fact has been taken into consideration. The objectives are defined as: minimising total completion time of jobs and maximising the reliability of system (minimising failure rate of machines). Since these objectives are conflict and complexity of the model is high, a non-dominated sorting genetic algorithm (NSGAII) is designed to find Pareto optimal solution for this problem. The Pareto optimal solutions resulted from this paper is used by decision maker for selecting the solution that satisfies her/his needs in different industrial environments.